Fundamentals of Entrepreneurship (ENT300) : i-Eazy Laundry / Mohamad Amirul Zaini... [et al.] - Zaini, Mohamad Amirul; Monsingah, Chrielnie; Matin, Zie Elcy; Ruslan, Irneh; Malubin, Jasli (2015)
Company description i-eAzy Laundry is a business of washing clothes, which provide the services 'pick and delivery' the customer item. The business is a partnership where the business will be started on 8 January 2016 which located at 1 18, Desa 11mu Batu 1, JalanSeberang 99111 Kota Samarahan, Sarawak. This location is situated in student area. Therefore, it will have a great potential market for this business. Besides that, the area also full of resident so that will allows they come to our laundry. The business will provide washing, drying and steam with the various type of softener so that the customer can choose freely. Our employee has 4 years' experience in the Laundry industry and can provide high quality work at a faster turnaround rate than any other local competitor. We will also prove highest quality facilities like washing machine expert